МОЖНИТЕ КРАТКИ ЛИЧНОЗАМЕНСКИ ФОРМИ ПРИ УДВОЈУВАЊЕТО НА ТРИВАЛЕНТНИТЕ ГЛАГОЛИ (Филологические заметки, 2019)
In this paper, we are going to present possible short pronouns about direct and indirect objects, used together with trivalent verbs in Macedonian language.